To move or not to move: roles and specificity of plant RNA mobility - Maizel, Alexis; Markmann, Katharina; Timmermans, Marja; Wachter, Andreas (Current opinion in plant biology, 2020)
Intercellular communication in plants coordinates cellular functions during growth and development, and in response to environmental cues. RNAs figure prominently among the mobile signaling molecules used. Many hundreds of RNA species move over short and long distances, and can be mutually exchanged in biotic interactions. Understanding the specificity determinants of RNA mobility and the physiological relevance of this phenomenon are areas of active research. Here, we highlight the recent progress in our knowledge of small RNA and messenger RNA movement. Particular emphasis is given to novel insight into the specificity determinants of messenger RNA mobility, the role of small RNA movement in development, and the specificity of RNA exchange in plant-plant and plant-microbe interactions.